A detailed DFT theoretical investigation of the mechanism of quinoline hydrogenation catalyzed by a (1,5-cyclooctadiene)rhodium(I) complex - Rosales, Merlín; Arrieta, Federico; Baricelli, Pablo; Colina, Angymileth; Izquierdo, Rodolfo [UNESP] (My University, 2025)
A detailed catalytic cycle for the hydrogenation of quinoline (Q) to 1,2,3,4-tetrahydroquinoline (THQ) catalyzed by a cationic rhodium complex containing a 1,5-cyclooctadiene (COD) ligand was computationally investigated by using DFT. It was found that the catalytically active species was [Rh(COD)(κN-Q)]+ and that the addition of each of the two dihydrogen molecules occurs through the initial coordination of dihydrogen forming η2-H2 intermediates, followed by the subsequent hydride transfer to Q and DHQ ligands (i.e., migratory insertion and reductive elimination), respectively. Except the reductive elimination of the THQ product, all of the elementary steps of the catalytic cycle were reversible, which is an important point in connection with the hydrogen storage models. Our theoretical DFT calculations are consistent with the experimental results previously reported, but additionally provides important information that allows us to have a deeper insight into the reaction mechanism and, therefore, to present a more detailed catalytic cycle for this reaction.
Keywords: 1; 5-cyclooctadiene; Density Functional Theory (DFT); Hydrogenation reversible; M06-L; Quinoline; Rhodium